Physical properties of lacustrine shale oil: A case study on the lower member of the Lucaogou Formation (Jimusaer Sag, Junggar Basin, NW China). (November 2022) - Shiju, Liu; Misch, David; Gao, Gang; Jin, Jun; Gang, Wenzhe; Yanjuan, Duan; Wu, Xinsong; Xiang, Baoli; Wang, Ming; Luo, Qingyong
Abstract: Shale oil generated by the lower member of the Lucaogou Formation, which was deposited under saline lacustrine conditions within the Jimusaer Sag of the Junggar Basin (NW China), is generally characterized by high density and viscosity. However, a strong spatial heterogeneity of physical properties is observed as well. In this paper, these spatial variations and their controlling mechanisms are evaluated from the perspective of the primary depositional environment, source rock thermal evolution and fractionation effects of primary migration. Based on a detailed organic petrological and geochemical characterization of the target interval within the key well JHBE, hydrous pyrolysis experiments conducted on representative source rock samples from well JHBE, as well as established methods of oil-source correlation subjected to oil samples from several regionally distributed producing shale oil wells, a predictive model of density and viscosity changes of crude oil was established. According to the findings of this study, the thermal evolution and sedimentary environment of source rocks are the main factors affecting the quality of crude oil, and the fractionation effect of primary migration has little effect. Crude oil density and viscosity at first increase up to peak oil maturity, followed by a decrease with further increasing thermal evolution of the source rock. Furthermore, if the source rocks experienced similar thermal histories, it was discovered that relatively low density and corresponding viscosity values are characteristic for crudes from source rocks which were formed in a relatively high salinity environment. In contrast, hydrocarbon generation of source rocks formed under relatively low salinity environments is slightly retarded in direct comparison, and the density and viscosity of the generated crude oil are both relatively high. This highlights that a detailed organic petrographical and geochemical evaluation of the target formation is crucial for the assessment of shale oil potential and production sweet spots in alginite-dominated lacustrine sedimentary environments. Highlights: Oil-source correlation of the lower member in the Lucaogou Formation are conducted. Crude oil density and viscosity control by thermal evolution are discussed from a new sight. The higher salinity is, the lower density of crude oil is.